Sensory substitution reveals a manipulation bias - Anja T. Zai (Nature Portfolio, 2020)
The challenge of sensory substitution as a therapeutic approach is to design systems that are well accepted by subjects. Here, in deaf songbirds, the authors substitute hearing with vision, suggesting substitution devices could provide sensory feedback for the key actions that are deprived.